Intraoperative frozen cytology of intraosseous cystic meningioma in the sphenoid bone - Na Rae Kim; Gie-Taek Yie (Journal of Pathology and Translational Medicine, 2020)
Meningiomas in bone are rarely subjected to fine-needle aspiration diagnosis, and those arising in the skull bone with a cystic presentation are rare. A 24-year-old woman presented with subdural hemorrhage, and subsequent radiology depicted an osteolytic mass-like lesion in the sphenoid bone. Intraoperatively, a solid and cystic hemorrhagic lesion mimicking an aneurysmal bone cyst was observed in the sphenoid bone with dural tearing. Frozen cytology showed singly scattered or epithelioid clusters of round to elongated cells intermixed with many neutrophils. Tumor cells had bland-looking round nuclei with rare prominent nucleoli and nuclear inclusions and eosinophilic granular to globoid cytoplasm in capillary-rich fragments. Histology revealed intraosseous meningothelial and microcystic meningioma (World Health Organization grade 1) in right lesser wing of the sphenoid bone. Considering its unusual location and cytologic findings, differential diagnoses included chordoma, chondroma, chondrosarcoma, and aneurysmal bone cyst. The present case posed a diagnostic challenge due to possible confusion with these entities.